Uma memória das lutas feministas brasileiras: 1976 a 1988 - Melo Hermes de Araujo, Hildete Pereira de (2019)
This article aims to narrate the arrival of the feminists of the generations of the 1960s and 1970s to the Brazilian political space and thus recover the history of these struggles and culminated in the writing of citizens' rights in the Brazilian Constitutional Charter of 1988. But this narrative was written as memorialist notes by the author who lived with passion these moments of the struggle for democracy in Brazil and her encounter with the feminist ideology that emerged, in those years, in the scenario of Brazilian society. Thus, these memoirs were constructed as follows: first a brief history of the feminist struggles throughout the first Republic, to situate the readers in the timid advances conquered by the Brazilian ones during those decades. She narrates the times of mobilization, conquest and defeat experienced by the Brazilian feminist movement, following the UN's call for the "International Women's Conference" in 1975, which allowed feminist activists, under the military regime, to create the Center for Brazilian Women (CMB). Emphasizes that this intense activism enabled women to have a pioneering participation in the management of national public policy. This was undoubtedly the most significant milestone in 1985, with the creation of the National Council for Women's Rights (CNDM), the public body responsible for this policy, and the victories won by women in the drafting of the 1988 Constitutional Charter, although several defeats occurred, as these memories show. These are explained by the strong sexism present both yesterday and today in Brazilian politics.